KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI MODEL PROJECT BASED LEARNING BERBANTUAN KAHOOT - Zaskia Mutia Herianti; Melisa; Hamdunah (Jurnal Ilmiah Matematika Realistik, 2026)
This study aims to determine the application of the Project Based Learning model to the mathematical problem-solving abilities of eleventh-grade students at SMAN I V Koto Timur. The research method used was a pre-experiment with a one-group pretest-posttest design. The research sample, namely class XI F2 as a sample class with the Kahoot-assisted Project Based Learning model. The research instrument was a descriptive test of problem-solving abilities, and data analysis used normality tests, homogeneity tests, and the wilcoxon test. The research was carried out in three stages: the preparation stage, the implementation stage, and the final stage. The novelty of this study lies in the integration of the Project Based Learning model with Kahoot as a gamified evaluation tool within the Merdeka Curriculum framework, which has not been widely studied in the context of high school mathematics learning. The results showed that students’ problem-solving abilities with the Kahoot-assisted Project Based Learning model were better than those before implementing the Kahoot-assisted Project Based Learning model. Thus, the Kahoot-assisted Project Based Learning model can be used as an innovative learning alternative to improve students’ mathematical problem-solving abilities.